High-temperature and radiation-resistant spinel-type ferrite coating for thermo-optical conversion in radioisotope thermophotovoltaic generators. (15th January 2022) - Wang, Hongyu; Xu, Zhiheng; Yuan, Zicheng; Liu, Kai; Meng, Caifeng; Tang, Xiaobin
Abstract: High-temperature radioisotope heat source surface coated with excellent performance of thermo-optical conversion coating can greatly improve thermophotovoltaic energy utilization. However, long-term high-temperature and radiation resistance of the thermo-optical conversion pose a great challenge. In this work, spinel-type ferrite thermo-optical conversion coating was proposed to improve the heat and irradiation stability and output power of a radioisotope thermophotovoltaic (RTPV) prototype. Under the continuous irradiation of 32.64 kGy for 24 h at 1400 K, the emissivity of the spinel-type ferrite thermo-optical conversion coating could maintain more than 90%. In addition, the surface morphology of the coating was changed under high temperature, which enhanced its surface emissivity. Spinel-type ferrite thermo-optical conversion coating was applied to the RTPV prototype, which achieved a maximum output power of 144.23 mW. Compared with the RTPV prototype without coating, the overall output increased to 181.51%. Spinel-type ferrite thermo-optical conversion coating showed great application potential in the fields of thermo-optical conversion and high-efficiency utilization of thermal energy. Highlights: Heat-resistant and irradiation-resistant thermo-optical conversion coating was designed. After 1400 K and 32.64 kGy tolerance tests, SFTOC coating maintained 90% thermo-optical emissivity. The maximum output power of RTPV with SFTOC coating increased by 81.51% and up to 144.23 mW. After four temperature cycles from 1000 K to 300 K, SFTOC maintained stable thermo-optical conversion.